Selection of solutions in a multi-objective environment: polymer extrusion a case study - Ferreira, José C. (2007)
A new methodology, based on a weight Stress Function Approach, to select the best solution (or set of solutions) from a Pareto frontier taking into account the preferences of the Decision Maker (DM), was proposed. This methodology is able to define the best region of the Pareto frontier from a weight vector defined by the DM. This methodology was tested in several benchmark problems from the literature and was applied to a real polymer extrusion problem. The methodology proposed is able to obtain solutions with physical meaning accordingly with the DM preferences.